EFEITOS DE MODIFICAÇÕES ESTRUTURAIS SOBRE A DIFUSIVIDADE TÉRMICA EFETIVA EM SISTEMAS COM DUPLA CAMADA MEDIDA PELA TÉCNICA DE CÉLULA FOTOACÚSTICA ABERTA - Somer, Aloisi (2016)
The generation of mechanical waves can be produced in the air in contact with the surface of a sample since a modulated light focus on that sample. This feature is well known, and there are several techniques and theoretical models to elucidate this process. One of the techniques used to measure such waves is the technique of cell Open Photoacoustic (OPC), and why it is can estimate the thermal diffusivity of a sample. The hypothesis in this thesis is that small structural changes in thin superficial layers can influence on effective thermal diffusivity measured by the OPC technique. Initially, it was carried out a review of mathematical models presented in the literature for samples with double layer, and the approach of a second thin layer. It has been found that the influence of a thin layer on a thick sample is negligible, and, therefore, the effective thermal diffusivity tends to the value of the thermal diffusivity of the bulk sample in all models. To check the influence of structural modification in a second thin layer were produced two sets of samples with two kinds of surface structural changes in samples with metallic volume. The first set was with changes in the proportions of rutile and anatase, the structural phases TiO2 film which was grown by thermal oxidation treatment in three types of titanium metal: two degrees of purity titanium, Ti and TiG2, and a TiG5 alloy (Ti-6Al-4V). The correlation of effective thermal diffusivity and the structural modification of layers grown by different thermal treatment (at 600 and 700ºC) in various treatment times was established. The effective thermal diffusivity determined by OPC is directly proportional to anatase quantity in the thermally grown layer of samples. In the second set were created different concentrations of structural martensite phase by mechanical polishing of austenitic AISI304 steel samples, having an austenitic volume. The effective thermal diffusivity values are influenced as the ratio martensite/austenite as the thickness of the sample. It was expected a decrease in effective thermal diffusivity values with decreasing the martensite quantity on the surface of samples as with the increase in the thickness of samples. This behavior was partially observed, however for small proportions of martensite and higher thickness values the effective thermal diffusivity increases. This feature can be associated with non-linear effects. Also, a method to check the thermal diffusivity values obtained by the OPC technique was proposed. This procedure comes from the dependency of the weight parameter thermoelastic bending C2, which depends on the thickness of the sample. If the dependence of C2 is as close to ls-3 confirms the values of thermal diffusivity. The method was tested for aluminum samples successfully. In conclusion, the variation in concentration of structural changes on sample´s surface and thin layers can influence the effective thermal diffusivity obtained by OPC technique, contrary to the theoretical models predict.